Hak Berpolitik Non-Muslim dalam Negara Modern: Analisis Pemikiran Abdullahi Ahmed An-Na’im Perspektif Siyāsah Syar’iyyah: The Political Rights of Non-Muslims in the Modern State: An Analysis of the Thought of Abdullahi Ahmed An-Na’im from the Perspective of Siyāsah Syar’iyyah - Rauzatul Nafisi; Jamhir; Shabarullah (Journal of Indonesian Comparative of Syari'ah Law, 2026)
This article examines the political rights of non-Muslim citizens in the context of the modern state by analyzing the thought of Abdullahi Ahmed An-Na‘im from the perspective of siyāsah shar‘iyyah. This issue is significant because classical Islamic jurisprudence generally framed the political status of non-Muslims within the limited category of ahl al-dhimmah, whereas the modern nation-state is founded upon the principle of equal citizenship. An-Na‘im proposes an alternative paradigm of a secular state that is not hostile to religion but instead guarantees freedom of religion and equal political rights for all citizens. Employing a qualitative library-based method with a normative–philosophical approach, this study explores An-Na‘im’s conception of non-Muslim political rights and assesses its compatibility with the framework of maqāṣid al-sharī‘ah. The main scholarly contribution of this study lies in its reconstruction of An-Na‘im’s thought within the framework of siyāsah shar‘iyyah, thereby extending contemporary discussions in Islamic political jurisprudence on the legitimacy of political equality for non-Muslims. The findings indicate that An-Na‘im’s ideas are substantively consistent with the core values of siyāsah shar‘iyyah, particularly the principles of justice (al-‘adl) and public interest (al-maṣlaḥah), despite their formal divergence from classical juristic formulations. The recognition of non-Muslim political rights can thus be understood as an actualization of the objectives of Islamic law, especially the protection of religion, life, intellect, property, and human dignity. Nevertheless, the implementation of An-Na‘im’s framework in Muslim-majority states raises conceptual and sociopolitical challenges, particularly regarding normative resistance to secularism and the reinterpretation of Islamic legal authority. Accordingly, An-Na‘im’s thought should be viewed as a critical ethical–conceptual framework rather than a directly applicable normative model without contextual adaptation.